The Tourist Destination Image of Penang: Is TDI Affected by Sociodemographic Factors and Does TDI Influence Conative Behavior? - Harris, Mary Ann (2008)
The purpose of this study is to investigate whether demographics plays a role in the formation of the tourists’ cognitive and affective image of the destination.